Courts: An Effective Venue to Promote Government Transparency? The Case of the Court of Justice of the European Union - Spahiu, Irma (Utrecht Journal of International and European Law, 2015)
This article aims to shed some light on the role of the Court of Justice of the European Union on transparency and access to documents. It uses case law as a method to investigate the potential of the Court of Justice jurisprudence for the protection of transparency as a general principle and access to documents as a fundamental right in the European Union. The article employs the concepts of Eurolegalism and the constitutionalisation of rights as a framework to examine the case law of the EU’s highest court. It focuses on the trends established by the Court on access rights by looking at some of the most influential cases that had made history through the years and analyzing their potential to create a body of a reformed administrative law in the EU pertaining transparency. While the Court of Justice may not be the ultimate solution to the problems of transparency in the Union, it has established itself as a driving force in the development of transparency and access rights regime in the EU and may affect their future trajectories in the face of legislative challenges.